Principles of modern grinding technology - Rowe, W. B. (William Andrew, 2009)
This book provides insights into modern grinding technology based on wide research and experience. It provides a concise treatment of the principles involved and shows how these lead on to the latest technology developments. The reader learns how to achieve high precision, fast removal rates, and reduced costs. Every aspect of the grinding process and machine comes under the searchlight to show step improvements. Superb grinding machines now produce optical quality finishes due to developments in process control and machine design. It is the same for extremely high removal rates. This book shows how best quality can be improved and costs brought down at the same time as output is increased. The book is aimed at practitioners, engineers, researchers, students, and teachers. The approach is direct, concise and authoritative. Progressing through each major element of the grinding system and then on to machine developments and process control, the reader becomes aware of all aspects of operation and design. Trends are described demonstrating key features. Covered topics include abrasives and super-abrasives, wheel design, dressing technology, machine accuracy and productivity, grinding machine design, high-speed grinding technology, cost optimization, ultra-precision grinding, process control developments, vibration control, coolants, and fluid delivery. Advances in the field are supported with references to leading research. Analysis is presented in later chapters and appendixes with new contributions to machine design, intelligent control, centerless grinding, fluid delivery, cost analysis, and thermal analysis for prediction and control of grinding temperatures. By selecting the right conditions, extremely high removal rates are achieved accompanied by low temperatures. ABOUT THE AUTHOR W. Brian Rowe is a research and consulting engineer, previously Professor and Director of Advanced Manufacturing Technology and Tribology Research Laboratory (AMTTREL) at Liverpool John Moores University in the UK. A multiple recipient of prizes from The Institution of Mechanical Engineers (IMECHE), Dr. Rowe has four decades of experience in academic and industrial positions concerned with machine tools, grinding processes, and tribology. His accomplishments include over 250 published papers, several books, international visiting professorships, and international consulting in industry. Trends in high precision and high speed grinding are explored Principles underlying improvements in machines and processes are explained Numerically worked examples give scale to essential process parameters Recent research findings and original contributions to knowledge are included A number of ultra-precision grinding machine developments are included.